A magnetic covalent organic framework as an adsorbent and a new matrix for enrichment and rapid determination of PAHs and their derivatives in PM2.5 by surface-assisted laser desorption/ionization-time of flight-mass spectrometry. Issue 26 (12th March 2019) - Zhang, Yanhao; Song, Yuanyuan; Wu, Jie; Li, Ruijin; Hu, Di; Lin, Zian; Cai, Zongwei
Abstract : Fe3 O4 @COFs served as an adsorbent and new matrix for SALDI-TOF-MS analysis of PAHs and their derivatives in PM2.5 with clear background, good reproducibility and sensitivity. Abstract : A magnetic covalent organic framework nanomaterial (Fe3 O4 @COFs) served as an adsorbent for enrichment and a new matrix for SALDI-TOF-MS analysis of PAHs and their derivatives in PM2.5 . The unique properties of Fe3 O4 @COFs in terms of high enrichment ability and matrix-free interference made it possible for sensitive analysis of low-concentration organic small-molecule pollutants in complex environmental samples.